Measurement of Supercritical Carbon Dioxide Capillary Trapping in Core Analysis - Pentland, C.; Iglauer, Stefan; El-Maghraby, R.; Okabe, H.; Tsuchiya, Y.; Blunt, M. (SPE, 2010)
Capillary trapping has been identified as a fast and effective method to render injected carbon dioxide (CO2) immobile as disconnected pore-scale droplets surrounded by brine. We measure trapped CO2 saturations in sandstones at conditions representative of storage locations. We compare the unsteady state and porous plate methods of achieving initial CO2 saturations before waterflooding to reach residual saturation. Brine and CO2 are equilibrated prior to injection to ensure immiscible displacements occur on the pore scale. The problems faced with un-equilibrated phases are discussed.The unsteady state and porous plate methods are shown to give different results in terms of maximum initial and residual saturations for Berea sandstone samples. With the unsteady state method maximum residual CO2 saturations of 25-28% are measured for corresponding maximum initial saturations of 35-40%. With the porous plate method a maximum residual saturation of 37% is measured for a maximum initial saturation of 90%. The implications for coreflood method selection during data gathering are discussed. The porous plate results are compared with oil-brine porous plate saturations measured on the same samples. CO2-brine residual saturations are shown to be slightly lower than the corresponding oil-brine measurements. We suggest that considerable carbon dioxide capillary trapping is possible in clean sandstones and discuss the implications for carbon storage in aquifers.